2011
DOI: 10.1111/j.1365-2710.2011.01251.x
|View full text |Cite
|
Sign up to set email alerts
|

Thiazolidenediones induce tumour-cell apoptosis through the Akt-GSK3β pathway

Abstract: Our data suggest that modulation of Akt-GSK3β pathway is involved in the cell death pathway engaged by TZDs in prostate cancer cells. This reveals another possible mechanism of TZDs on apoptosis in prostate cancer. Inhibition of the Akt-GSK3β cascade may be a useful approach in prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Furthermore, glitazones inactivated GSK-3b, which exerts essential roles in prostate cancer growth and in androgen-independent phenotype (Zhu et al 2012). Very noteworthy, the GSK-3b inhibitor lithium sensitized prostate cancer cells to glitazone cytotoxicity (Zhu et al 2012). Antioxidant edible anthocyanins reduce obesity and the severity of the metabolic syndrome (Qin and Anderson 2012).…”
Section: Mutual Interactions Between Gsk-3b and Ppar-c Pathways And Rmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, glitazones inactivated GSK-3b, which exerts essential roles in prostate cancer growth and in androgen-independent phenotype (Zhu et al 2012). Very noteworthy, the GSK-3b inhibitor lithium sensitized prostate cancer cells to glitazone cytotoxicity (Zhu et al 2012). Antioxidant edible anthocyanins reduce obesity and the severity of the metabolic syndrome (Qin and Anderson 2012).…”
Section: Mutual Interactions Between Gsk-3b and Ppar-c Pathways And Rmentioning
confidence: 98%
“…The apoptosis-triggering efficacy of glitazones on prostate cancer cells involved the inhibition of Akt phosphorylation. Furthermore, glitazones inactivated GSK-3b, which exerts essential roles in prostate cancer growth and in androgen-independent phenotype (Zhu et al 2012). Very noteworthy, the GSK-3b inhibitor lithium sensitized prostate cancer cells to glitazone cytotoxicity (Zhu et al 2012).…”
Section: Mutual Interactions Between Gsk-3b and Ppar-c Pathways And Rmentioning
confidence: 99%
“…Previous studies showed that LiCl also possess antineoplastic effects in a variety of cancers including colorectal cancer [ 10 ], gastric cancer [ 11 ], and neuroblastoma [ 12 ]. It was shown that anti-neoplastic action of LiCl primarily depends on the inhibition of glycogen synthase kinase 3-beta [ 13 ].…”
Section: Introductionmentioning
confidence: 99%